The effect of cooling media on impact toughness and tensile strength after GTAW welding of aluminum alloy - Margi Luhur, Galih Maulana; Salahudin, Xander; Hastuti, Sri (Journal of Welding Technology, 2025)
Aluminum 5083 is extensively utilized in ship hull construction due to its high impact resistance and superior tensile load capacity, offering a lightweight alternative to steel. In maintenance procedures, welding is a fundamental method for repairing damaged sections, with Gas Tungsten Arc Welding (GTAW) favored for its precise thermal control and minimal distortion. Among the critical factors influencing weld quality, the post-weld cooling process significantly affects the resulting microstructure and mechanical performance. This study examines the effects of various cooling media—namely, Bromus Soluble Oil Cutting Coolant, Castor oil, and Mesran Super SAE 20W-50 oil—on the impact toughness and tensile strength of GTAW-welded Aluminum 5083 with a current of 325 A and 220 V AC voltage. Mechanical properties were evaluated through Charpy impact testing and tensile testing by ASTM standards. The findings reveal that Bromus coolant yielded the highest impact toughness at 0.264 J/mm², whereas Bromus coolant achieved the highest tensile strength at 12.893 Kgf/mm². These results underscore the critical role of cooling medium selection in enhancing the mechanical integrity and durability of welded aluminum structures, as the bromus coolant significantly outperformed alternatives in both impact and tensile assessments